Validation of the German Montreal-Cognitive-Assessment-H for hearing-impaired - Völter, Christiane; Fricke, Hannah; Faour, Sarah; Lueg, Gero; Nasreddine, Ziad S.; Götze, Lisa; Dawes, Piers (Frontiers in Aging Neuroscience, 2023)
Background: Hearing loss and dementia are highly prevalent in older age and often co-occur. Most neurocognitive screening tests are auditory-based, and performance can be affected by hearing loss. To address the need for a cognitive screening test suitable for people with hearing loss, a visual version of the Montreal-Cognitive-Assessment was developed and recently validated in English (MoCA-H), with good sensitivity and specificity for identifying cases of dementia. As the MoCA is known to perform differently across languages, revalidation of the German MoCA-H was necessary. The aim of the present study was to assess the diagnostic accuracy of the German MoCA-H among those with normal cognition, mild cognitive impairment (MCI) and dementia and to determine an appropriate performance cut- off. Material and methods: A total of 346 participants aged 60 to 97 years (M = 77.18, SD = 9.56) were included; 160 were cognitively healthy, 79 with MCI and 107 were living with dementia based on the GPCOG and a detailed medical questionnaire as well as a comprehensive examination by a neurologist in case of cognitive impairment. Performance cut-offs for normal cognition, MCI and dementia were estimated for the MoCA-H score and z-scores using the English MoCA-H cut-off, the balanced cut-off and the Youden’s Index. Results: A mean score of 25.49 (SD = 3.01) points in the German MoCA-H was achieved in cognitively healthy participants, 20.08 (SD = 2.29) in the MCI and 15.80 (SD = 3.85) in the dementia group. The optimum cut-off for the detection of dementia was ≤ 21 points with a sensitivity of 96.3% and a specificity of 90%. In the MCI group, a cut-off range between 21 and 24 points is proposed to increase diagnostic accuracy to a sensitivity and specificity of 97.5% and 90%, respectively. Conclusion: The German MoCA-H seems to be a sensitive screening test for MCI and dementia and should replace commonly used auditory-based cognitive screening tests in older adults. The choice of a cut-off range might help to better reflect the difficulty in clinical reality in detecting MCI. However, screening test batteries cannot replace a comprehensive cognitive evaluation.